2020
DOI: 10.1002/pchj.355
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related Internet use and treatment adherence: A transdiagnostic comparison of outpatients with major depressive disorder and schizophrenia

Abstract: Treatment adherence is relevant for clinical and economic outcome in affective disorders as well as psychosis. Knowledge concerning the disease and its treatment might influence patients' willingness to follow the health-care providers' recommendations and mutual decision-making. In the current study, we investigated how Internet surfing for health-related issues and attitude toward the relevance of the online information impact treatment adherence in major depressive disorder (MDD) and schizophrenia (SZ). A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…It is conceivable that adherence to precision medicine tools can be as common as that for pharmacological treatment in individuals with mental illness. As several factors, including access to scientifically reliable and valid evidence, 69 might substantially influence adherence, disseminating information and involving patients in shared decision-making could favor the implementation of precision psychiatry tools. 70 Figure 1 illustrates some of the main barriers and opportunities for precision psychiatry.…”
Section: Barriers To Precision Medicine In Psychiatrymentioning
confidence: 99%
“…It is conceivable that adherence to precision medicine tools can be as common as that for pharmacological treatment in individuals with mental illness. As several factors, including access to scientifically reliable and valid evidence, 69 might substantially influence adherence, disseminating information and involving patients in shared decision-making could favor the implementation of precision psychiatry tools. 70 Figure 1 illustrates some of the main barriers and opportunities for precision psychiatry.…”
Section: Barriers To Precision Medicine In Psychiatrymentioning
confidence: 99%
“… 28 Only one study has a sample size of less than 100. 29 Most studies (12 of 17) were conducted in outpatient clinics, but 4 used an online platform, two were conducted in the community, and one was conducted in an inpatient setting. One of the studies was undertaken in both an outpatient clinic setting and an online platform.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies used validated self-reported questionnaires to measure medication adherence. The most common was the Morisky Medication Adherence Scale (7 of 11 studies), 28 , 36 37 , 41 43 two studies used the Medication Adherence Rating Scale, 29 , 40 while two studies used self-validated adherence rating scales. 33 , 34 The rest of the studies used non-standardised scales to measure medication adherence, including four studies that measured missed medications over specific durations such as three days, one week, or 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicate that negative symptoms, mania, and social cognition are the strongest predictors across diagnoses. Zavorotnyy, Ehrlich, and Nenadic () adopted a transdiagnostic approach to compare outpatients with major depressive disorder and schizophrenia spectrum disorders on health‐related Internet use and treatment adherence. S. Wang et al () further examined the potential moderated and mediated roles of sense of belongingness and suicidal behavior in patients with mental disorders.…”
mentioning
confidence: 99%